Dopamine and Effort-Based Decision Making - Kurniawan, Irma T.; Guitart-Masip, Marc; Dolan, Ray J. (Frontiers in Neuroscience, 2011)
Motivational theories of choice focus on the influence of goal values and strength of reinforcement to explain behavior. By contrast relatively little is known concerning how the cost of an action, such as effort expended, contributes to a decision to act. Effort-based decision making addresses how we make an action choice based on an integration of action and goal values. Here we review behavioral and neurobiological data regarding the representation of effort as action cost, and how this impacts on decision making. Although organisms expend effort to obtain a desired reward there is a striking sensitivity to the amount of effort required, such that the net preference for an action decreases as effort cost increases. We discuss the contribution of the neurotransmitter dopamine (DA) towards overcoming response costs and in enhancing an animal’s motivation towards effortful actions. We also consider the contribution of brain structures, including the basal ganglia (BG) and anterior cingulate cortex (ACC), in the internal generation of action involving a translation of reward expectation into effortful action.